Improving Reading Comprehension Through Information Transfer Activity of The Eleventh Grade Students of Senior High School - Mawardin, Ilmuislami; Kamarudin, Abdul; Anggreni, Afrillia; Mukrim, Mukrim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The objective of this research is to find out whether or not implementing information transfer technique improves the reading comprehension of eleventh grade students. The researcher used a pre-experimental research design. The population of this study was the eleventh-grade students of SMAN 3 Palu, and the sample was the eleventh-grade social science IV which totaled 33 students. The researcher used a purposive sampling technique and adopted one group pre-test and post-test design. The pre-test is used to measure the students' reading comprehension before treatment, and the post-test is used to measure students' comprehension after treatment. The results of data analysis indicates that there is a significant difference of the students' achievement in pre-test and post-test. It shows that the mean score of the pre-test is 53.58 and the mean score of post-test is 82.27. The t-counted (15.76) is greater than the t-table (1.694) it means that the hypothesis of this research is accepted. In conclusion, implementing the information transfer technique improves reading comprehension of the eleventh grade students of SMAN 3 Palu.